Monitoring managed forest structure at the compartment-level under different silvicultural heritages: An exploratory data analysis in Italy. (2nd April 2016) - Becagli, Claudia; Bertini, Giada; Di Salvatore, Umberto; Fabbio, Gianfranco; Fabrizio, Ferretti; Salvati, Luca
ABSTRACT: The more and more diffused multifunctional role addressed nowadays to public forests, calls for targeted analysis aimed at highlighting the overall outcome of different practices implemented on the same forest compartment, according to the locally prevailing function. This study was carried out in four Italian beech forests across a latitudinal gradient representative of multiple management history, stand structure, and dominant stand age. We analyze forest structure at the compartment scale before and after silvicultural practices. We aim to explore relationships and similarities between 10 stand attributes (mensurational and structural variables) to identify relevant indicators for the monitoring and management of forest ecosystems. Results indicate changing patterns of correlation and similarity among mensurational variables following practice implementation. A sensitivity gradient to silvicultural practice was finally identified within the four sites investigated as a result of the diverging stand structure. Our approach suggests a way and provides an insight for the design of adaptive forestry management practices required to meet environmental targets, in addition to the already acknowledged supply of primary goods and services.